Unmanageable Youth. Education and imaginary, avert cynicism (Praxis Educativa, 2022)
In the context of the effects generated of the discredit of the collective and institutions, of the dissolution of social regulations and the individualization of the subjects. The article develops the argument that in order to configure a subjectivity and an identity for themselves and others, teenagers and youths have to conform to the individual behavior patterns determined by parents and teachers as if they were generalizable regulatory frameworks. And with this as if, gradually, setting ways of cynic action against what is said to be the right way to act. This relates to the challenges that in school context cause to classify them as an anomic youth in which solutions only meet with individualized ways of sentence, without pondering that there are more ways of attention linked to the possibility to regain symbolic strength of regulation and the imaginary creation.
Keywords: youth; education; institutions; imaginary